Reflections on internationalization: quo vadis UNIOESTE? - Christ, Gabriela Daiana; Frohlich, Samantha; Mattiello, Rafael (Revista Expectativa, 2021)
Universities are institutions whose commitments go beyond the fields of teaching, research, and outreach. In a society that increasingly requires changes, cooperating with other actors must be a path to be followed. At the same time, internationalization has become a priority appearing on many Higher Education institutions’ agendas. However, it is an open question how universities should manage the new demands proposed by society in a very fast challenging world. Therefore, the aim of this article is to provide a framework for strategic priorities which outlines steps and activities that the Western Paraná State University (UNIOESTE) should adopt as part of this transformation project through the lens of the Project Model Canvas (FINOCCHIO JUNIOR, 2013). The methodology is characterized as a qualitative study, with an exploratory character, with the collection of data through documentary research. The results show that to operate successfully in the increasingly globalized environment, Unioeste must continue to foster a commitment to internationalization and make significant efforts to integrate the international dimension into key areas of operation. RESUMO As universidades são instituições cujos compromissos vão além dos campos do ensino, da pesquisa e da extensão. Em uma sociedade que exige cada vez mais mudanças, a cooperação com outros atores deve ser um caminho a ser percorrido. Paralelamente, a internacionalização passou a ser uma prioridade que aparece na agenda de muitas Instituições de Ensino Superior. No entanto, é uma questão em aberto como as universidades devem gerenciar as novas demandas propostas pela sociedade em um mundo acelerado e desafiador. Portanto, o objetivo deste artigo é fornecer um quadro de prioridades estratégicas que delineie as etapas e atividades que a Universidade Estadual do Oeste do Paraná (Unioeste) deve adotar como parte desse projeto de transformação sob a ótica do Project Model Canvas (FINOCCHIO JUNIOR, 2013). A metodologia caracteriza-se como um estudo qualitativo, de caráter exploratório, com coleta de dados por meio de pesquisa documental. Os resultados mostram que, para atuar com sucesso em um ambiente cada vez mais globalizado, a Unioeste deve continuar a promover o compromisso com a internacionalização e fazer esforços significativos para integrar a dimensão internacional em áreas-chave de atuação.